Evaluative Perception of Homestead Farmers in Relation to Appropriateness of Farming Systema and Cropping Patterns - Babu M N (Department of Agricultural Extension, College of Horticulture, 1995)
The study was undertaken in 18 selected panchayats of central zone comprising of Palakkad, Thrissur and Ernakulam districts, with a view to identify the farming systems and cropping patterns adopted in homesteads. The evaluative perception of the farmers in relation to the appropriateness of farming systems and cropping patterns adopted in homesteads, their level of knowledge on scientific practices and extent of adoption of scientific and indigenous practices were also studied. The sample consisted of 180 homestead farmers selected at random. Data were collected using a well-structured interview schedule developed for the purpose. Suitable statistical techniques were employed in the analysis of data. The study revealed that the homesteads of central zone were of unique nature in the sense that they comprised of a dwelling unit, with/without extended garden of wet land rice, monocrop rubber or additional crop land which acted as satellite units of the homestead. The major farming system identified was homesteads with crop components, livestock and extended garden, of which coconut based homesteads were predominant. In many of the homesteads, a multi- storied cropping pattern was in vogue whereas that of wet land was rice- rice- fallow. A good majority of the farmers were in the medium category with reference to their evaluative perception, level of knowledge and extent of adoption. Among the independent variables, extension participation, information sources used, economic motivation and annual income were found important in predicting the variations in evaluative perception. Education, extension participation, information sources used and value orientation were significantly correlated with level of knowledge. Education, farm size, extension participation, annual income and economic motivation were significantly correlated with extent of adoption. Evaluative perception of farmers was positively and significantly correlated with their level of knowledge and extent of adoption. Nearly half of the respondents were found adopting indigenous practices. Prohibitive cost of inputs was perceived as most important constraint followed by high labour cost. The study pointed out to the urgent need of effective measures to control the escalating rate of conversion of crop land to monocrop rubber and for purposes other than agriculture, and also the important role of these homesteads in conserving the agro- ecosystem and maintaining the environmental equilibrium. It also emphasized the need for an appropriate strategy for development of the homesteads, preferably on watershed area basis, by co-ordinating all the agencies directly or indirectly involved to ensure realistic, meaningful and sustainable agro-ecosystem management.